(untitled) (Huellas, 2022)
Various organizations of horticultural producers have developed short marketing circuits, which seek to constitute themselves as alternatives to traditional supply channels. The network of agroecological bags that the Colonia 20 de Abril "Darío Santillán" has implemented from Jáuregui (Luján, Buenos Aires) is one of them; it has expanded over more than a dozen parties and promoted fair trade in healthy foods. This article seeks to characterize this proposal, within the framework of the horticultural dynamics of the Metropolitan Area of ​​Buenos Aires (AMBA) and from the study of the sales nodes, as a new subject in the commercial mediation of vegetables, whose interests and motivations give new meanings to commercial exchange. The results arise from an ongoing research where farm tours and interviews with producers and node referents were carried out from 2018 to the present. Research delves into the following axes: territorial, the origin of the intermediaries, degree of commitment of the actors, individual or collective character of the commercial enterprise, as a methodological contribution for the study of these enterprises.